PRICE AND INFORMATION TRANSPARENCY IN DIGITAL SHARIA TRADING AS AN ETHICAL CHALLENGE FOR ISLAMIC BUSINESS IN THE HALAL MARKETPLACE - Miftahul Jannah (Mukhtasab: Journal of Economics and Islamic Business, 2026)
The rapid development of digital technology has significantly transformed Sharia-based commercial practices, leading to the rapid growth of halal marketplaces as platforms for Islamic digital trade. While these marketplaces aim to facilitate transactions that comply with Islamic principles, emerging ethical challenges particularly related to price and information transparency have raised critical concerns. In digital environments, consumers depend heavily on information provided by sellers and platforms, creating potential information asymmetry that may undermine the principles of honesty, justice, and mutual consent emphasized in Islamic business ethics. This study examines the issue of transparency in Sharia-based digital transactions by focusing on price disclosure and information clarity within halal marketplaces. This research employs a qualitative normative empirical approach, integrating Islamic business ethics theory with empirical observations of digital marketplace practices. Data were collected through document analysis, observation of marketplace interfaces, and in-depth review of relevant literature on Islamic ethics and digital commerce. The analysis is guided by key principles of Islamic business ethics, including honesty (ṣidq), transparency (shafāfiyyah), justice (ʿadl), trustworthiness (amānah), and mutual consent (tarāḍin). The findings reveal that although halal marketplaces generally display prices and product information, transparency is often partial and procedural rather than substantive. Hidden costs, conditional pricing, incomplete product descriptions, and unclear transactional terms contribute to persistent information asymmetry and weaken ethical compliance. The study concludes that transparency in Islamic digital commerce is a moral imperative rather than a technical feature. Strengthening ethical governance, improving information disclosure, and integrating Islamic ethical principles into platform design are essential for ensuring genuine Sharia compliance. These findings offer important ethical and practical implications for halal marketplace operators, digital Sharia business actors, regulators, and future research in Islamic digital economics.